Unprecedented 4,9‐Seco‐Oplopanane and Seven Drimane Sesquiterpenoids from the Chinese Liverwort Lejeunea flava (Sw.) Nees - Zhu, Ming‐Zhu; Li, Yi; Zhou, Jin‐Chuan; Wang, Tian; Qian, Li‐Lin; Zhang, Jiao‐Zhen; Han, Jing‐Jing; Xu, Ze‐Jun; Shen, Tao; Lou, Hong‐Xiang (Chemistry & biodiversity, 2022)
An unprecedented 4,9‐seco‐oplopanane (1), two undescribed drimane epimers (2 and 3), and five known drimane sesquiterpenoids (4–8) were isolated from the Chinese liverwort Lejeunea flava (Sw.) Nees. The structures of the new sesquiterpenoids were determined using nuclear magnetic resonance spectroscopy, electronic circular dichroism calculations, and single‐crystal X‐ray diffraction measurements. The inhibitory capacity of the new compounds against nitric oxide production in lipopolysaccharide‐induced RAW 264.7 murine macrophages, along with the cytotoxicity of the new compounds against A549 and HepG‐2 human cancer cell lines, were discussed.